Alec Wilder - Lambert, Philip, 1958- (American composers., 2013)
The music of Alec Wilder (1907-1980) blends several American musical traditions, such as jazz and the American popular song, with classical European forms and techniques. Wilder's musical oeuvre ranged from sonatas, suites, concertos, operas, ballets, and art songs to woodwind quintets, brass quintets, jazz suites, and hundreds of popular songs. In this biography and critical investigation of Wilder's music, the author chronicles Wilder's early work as a part-time student at the Eastman School of Music, his ascent through the ranks of the commercial recording industry in New York City in the 1930s and 1940s, his turn toward concert music from the 1950s onward, and his devotion late in his life to the study of American popular songs of the first half of the twentieth century.